12 tips on how to have a good worklife balance - Abdullah, Nasiha; Abdul Talib, Nurafida; Mohamad Azmin, Nur Azwani; Adenan, Nur Dalila; Ngah, Nazlin Emieza (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
A harmonious interaction between your personal and professional lives is what is meant by "healthy work-life balance". It entails actively prioritizing self-care and well-being while juggling your career and personal obligations.